High-rate carbon nanosphere self-assembled film electrode and preparation method thereof
By densifying and catalytically graphitizing self-assembled nano-hydrogel films, high-density carbon nanosphere self-assembled thin film electrodes were prepared, solving the problem of low density in existing carbon electrode materials and achieving sodium-ion battery performance with high volumetric energy density and power density.
Patent Information
- Application Number
- CN202410974346.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2026-01-20
AI Technical Summary
Existing carbon electrode materials have low density, making it difficult to form sodium-ion batteries with high volumetric energy density and power density. Furthermore, they require inactive materials for preparation, which leads to increased resistance and hindered ion/electron transport.
High-density carbon nanosphere self-assembled thin film electrodes were prepared by densification and catalytic graphitization of self-assembled nanohydrogel membranes, forming a continuous electronic conductive network and three-dimensional ion transport channels, avoiding the use of conductive agents and binders.
This technology enables rapid electron/ion transport in high-density carbon thin-film electrodes, improving the volumetric capacity and electrode density of sodium-ion batteries, simplifying the fabrication process, and reducing costs.
Smart Images

Figure CN121366877A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of preparation of materials and application of sodium ion battery negative electrode, and mainly relates to a high-rate carbon nanosphere self-assembled film electrode and a preparation method thereof. BACKGROUND
[0002] Sodium ion batteries have attracted increasing attention in sustainable energy storage systems due to their low cost and excellent comprehensive performance. However, the anxiety about the limited use time of portable electronic devices or the limited running mileage of electric vehicles is becoming more and more prominent. In order to solve this problem, it is urgent to develop advanced energy storage devices. Especially, the energy storage devices with high volume energy density and power density at the same time, which help to store energy in smaller space and at higher rate. Carbon materials are widely considered as one of the most promising sodium ion storage electrode materials due to their excellent cost-effectiveness and electrochemical activity. Unfortunately, the efforts made on compact carbon-based electrodes so far seem to be less.
[0003] Most of the existing preparation methods of carbon electrode materials are to take biomass or polymer as precursor, and prepare by direct carbonization method, activation method, hard template method and soft template method, etc. The obtained carbon material is usually in powder form, and has a low tap density (0.3-0.7 g cm -3 ), and it is difficult to obtain high volume performance. In addition, non-active substances (conductive carbon black and binder) are needed to assist the preparation of electrodes when used as electrode materials, which leads to further reduction of electrode density, increase of inter-particle resistance, and hindering of ion / electron transmission. These problems inevitably hinder the full release of Na + storage capacity of the prepared active material. SUMMARY
[0004] The present application aims to solve the shortcomings of the existing compact carbon electrode preparation technology, and provides a high-rate carbon nanosphere self-assembled film electrode and a preparation method thereof. The preparation process is simple and controllable, and the cost is low, which is suitable as an electrode material for high-rate sodium ion batteries. Through the densification and catalytic graphitization process of the self-assembled nanohydrogel film, the present application simply and controllably synthesizes a carbon nanosphere self-assembled dense carbon film with a density of 1.18 g cm -3 (about 51.3% of the theoretical density of graphite). These small enough and interlocked nanocarbon spheres (<100 nm) form an interconnected electron conduction network, and at the same time, the self-assembled architecture spontaneously generates a network topology ion transmission channel, thereby realizing compact and fast sodium ion storage performance (107 mA h cm -3 @50 Ag -1 ).
[0005] The purpose of the present application can be achieved by the following process:
[0006] In a first aspect, the present application provides a preparation method of a high-magnification carbon nanosphere self-assembled film electrode, comprising the following steps:
[0007] Step one: adding a poorly soluble calcium salt into a sodium alginate solution, and then adding a gluconolactone aqueous solution to obtain a sodium alginate hydrogel;
[0008] Step two: evaporative-induced drying of the sodium alginate hydrogel to obtain a sodium alginate film;
[0009] Step three: soaking the sodium alginate film in a Fe 3+ solution to crosslink and form a ferric alginate film;
[0010] Step four: carbonizing the ferric alginate film by calcination, and then etching by acid washing to obtain the product.
[0011] As an embodiment of the present application, in step one, the poorly soluble calcium salt includes any one of a nano-CaCO3 suspension and a nano-CaSO4 suspension.
[0012] As an embodiment of the present application, in step one, the mass ratio of the poorly soluble calcium salt, the gluconolactone and the sodium alginate is 5-7:7-9:40.
[0013] In some preferred embodiments, the mass concentration of the nano-CaCO3 suspension is 0.5-0.7 wt.%, the mass concentration of the gluconolactone aqueous solution is 0.7-0.9 wt.%, and the mass concentration of the sodium alginate solution is 1.8-2.2 wt.%.
[0014] As an embodiment of the present application, in step one, the poorly soluble calcium salt is stirred after being added into the sodium alginate solution. The stirring is sufficient to ensure that the poorly soluble calcium salt nanoparticles are uniformly dispersed between the sodium alginate chain segments, and since the poorly soluble calcium salt nanoparticles are not hydrolyzed, the obtained mixture is still a solution with fluidity.
[0015] As an embodiment of the present application, in step one, the gluconolactone aqueous solution is subjected to ultrasonic treatment after being added, and then is shaped and placed. The purpose of the ultrasonic treatment is to eliminate bubbles.
[0016] The present application utilizes the weak acidity of the gluconolactone to reduce the pH value of the mixed solution, control the hydrolysis of the poorly soluble calcium salt nanoparticles and slowly release Ca 2+ , and then realize the in-situ spontaneous crosslinking of the sodium alginate and the uniformly dispersed Ca 2+ , to obtain a homogeneous large sodium alginate hydrogel; by contrast, since the traditional method is to directly add the sodium alginate into the metal ion solution, the crosslinking speed of the two is too fast, and a non-homogeneous hydrogel is usually obtained, which is difficult to form a smooth sodium alginate film required subsequently.
[0017] As an embodiment of the present application, in step two, the temperature of the evaporation-induced drying is 20-40℃, and the time is 20-30h. If the temperature of the air-drying oven is too low, the drying time will be prolonged; if the temperature is too high, the water will evaporate too fast, which will cause the film to wrinkle.
[0018] The evaporation-induced drying process of the present application can remove the water and large pores in the bulk sodium alginate hydrogel. The capillary force promotes the close stacking of the loosely distributed alginate chains, and finally forms a smooth, homogeneous and mechanically excellent sodium alginate film, which can be used as a precursor for the subsequent preparation of dense carbon film. In contrast, the freeze-drying of the hydrogel can only obtain a brittle and porous alginate aerogel, which is difficult to further form a dense derivative carbon material, and cannot form a thin film electrode.
[0019] As an embodiment of the present application, in step three, the Fe 3+ The concentration of the solution is 0.08-0.15mol / L, and the crosslinking time is 20-30h. Since metal ions usually affect the microstructure of alginate-derived carbon materials, Fe 3+ As a crosslinking ion, it is used to utilize the low-temperature catalytic graphitization characteristics of iron, which helps the morphological transformation of alginate-derived carbon during carbonization.
[0020] In some preferred embodiments, the Fe 3+ The solvent used in the solution includes a mixed solution of deionized water and ethanol with a volume ratio of 10:1-3. The Fe 3+ The solution includes one of Fe(NO3)3, FeCl3, and Fe2(SO4)3.
[0021] As an embodiment of the present application, in step four, the calcination carbonization is heated to 750-850℃ at a heating rate of 4-6℃ / min, and the temperature is kept for 0.5-1h. During the carbonization process, Fe atoms can catalyze the rearrangement of amorphous carbon atoms to form a graphite structure, which has a high electrical conductivity (38.6S cm -1 ).
[0022] Further, the calcination carbonization is carried out in an inert atmosphere, and the flow rate of the inert atmosphere is 0.6-0.8L / min.
[0023] In some preferred embodiments, the calcination process comprises: calcining the iron alginate film sandwiched between two quartz glasses in an inert atmosphere, the flow rate of the inert atmosphere being 0.6-0.8 L / min; the calcination temperature being 780-830℃, the heating rate being 4-6℃ / min, and the time being 0.5-3h. The quartz glass can apply a certain pressure to the polymer film, avoid the structure bending caused by the weight loss of the polymer during the high-temperature process, and thus ensure that the obtained carbonized product remains a flat film with certain flexibility.
[0024] As an embodiment of the present application, in step four, the acid used in the acid pickling etching comprises 1.8-2 mol / L hydrochloric acid, the temperature of the acid pickling etching is 90-110℃, and the time is 20-30h. The acid pickling etching removes Fe3C.
[0025] As an embodiment of the present application, in step four, after the acid pickling etching, cleaning (to neutral) and vacuum drying are performed to obtain a carbon nanosphere self-assembled film electrode; the temperature of the vacuum drying is 100-110℃, and the time is 20-30h.
[0026] Compared with the cross-linked Fe 3+ Compared with the carbon aerogel powder obtained through the freeze-drying and carbonization processes, the dense carbon film obtained by the present application can have high electrode density and abundant ion transmission channels, and can be directly used as an electrode.
[0027] In a second aspect, the present application provides a high-rate carbon nanosphere self-assembled film electrode obtained by the preparation method.
[0028] Compared with the prior art, the present application has the following advantages:
[0029] 1. The present application removes the large pores in the homogeneous alginate hydrogel by evaporation-induced drying, obtains a dense sodium alginate film, and then prepares a carbon film electrode with a density as high as 1.18 g cm -3 The 50-100 nm carbon spheres serve as building units to form a continuous electron conductive network, and the self-assembled structure of the carbon nanospheres spontaneously generates three-dimensional ion transmission channels, which can be used for fast electron / ion transmission, thereby improving the volume specific capacity of the carbon film electrode, i.e. realizing compact and fast sodium ion storage performance.
[0030] 2. The carbon film prepared by the present application can be directly used as an electrode without introducing other low-density inert components such as conductive agents and binders for assisting electrode assembly, which can further improve the continuous conductivity and volume energy density (i.e. volume specific capacity) of the electrode.
[0031] 3、The raw materials used in the application are easy to obtain, the preparation method is simple, the process is easy to control, and the cost is low, so the application has good application prospect in the field of sodium ion batteries. BRIEF DESCRIPTION OF DRAWINGS
[0032] Other features, objects, and advantages of the application will become more apparent with reference to the following non-limiting description of embodiments, when read together with the accompanying drawings, in which:
[0033] Figure 1 Optical photograph of the homogeneous sodium alginate hydrogel prepared for Example 1;
[0034] Figure 2 Scanning electron microscope photograph of the carbon nanosphere self-assembled thin film electrode prepared for Example 1;
[0035] Figure 3 X-ray diffraction spectrum of the carbon nanosphere self-assembled thin film electrode prepared for Example 1;
[0036] Figure 4 N2 adsorption / desorption isotherm and pore size distribution graph of the carbon nanosphere self-assembled thin film electrode prepared for Example 1;
[0037] Figure 5 Rate performance graph of the carbon nanosphere self-assembled thin film electrode prepared for Example 1 as a sodium ion negative electrode material;
[0038] Figure 6 Sodium ion diffusion coefficient graph of the carbon nanosphere self-assembled thin film electrode prepared for Example 1;
[0039] Figure 7 Rate performance graph of the carbon nanosphere self-assembled thin film electrode prepared for Examples 2 and 3 as a sodium ion negative electrode material;
[0040] Figure 8 Optical photograph of the non-homogeneous sodium alginate hydrogel prepared for Comparative Example 1;
[0041] Figure 9 Optical photograph of the iron alginate aerogel prepared for Comparative Example 2;
[0042] Figure 10 Scanning electron microscope photograph of the porous carbon aerogel powder prepared for Comparative Example 2;
[0043] Figure 11 Rate performance graph of the porous carbon powder-based electrode prepared for Comparative Example 2 as a sodium ion negative electrode material;
[0044] Figure 12 Sodium ion diffusion coefficient graph of the porous carbon powder-based electrode prepared for Comparative Example 2. DETAILED DESCRIPTION
[0045] The application will be described in detail below with reference to the accompanying drawings and specific embodiments. The following examples are implemented under the technical solutions of the application, and detailed embodiments and specific operation processes are provided, which will help those skilled in the art to further understand the application. It should be pointed out that the protection scope of the application is not limited to the following examples, and several adjustments and improvements made under the concept of the application also belong to the protection scope of the application.
[0046] Example 1
[0047] Step one, 1.0 g of sodium alginate was dissolved in 50 ml of deionized water, and after 48 h of sufficient stirring, a 2 wt.% sodium alginate solution was obtained.
[0048] Step two, 0.15 g of calcium carbonate and 0.20 g of gluconolactone were weighed into 25 ml of deionized water, respectively, and ultrasonic stirring was performed to form a 0.6 wt.% CaCO3 suspension and a 0.8 wt.% gluconolactone solution.
[0049] Step three, the solution prepared in step two was added to the solution prepared in step one, and after uniform magnetic stirring, ultrasonic treatment was performed for 20 s to remove air bubbles.
[0050] Step four, immediately transferred to a culture dish with a height of 3 mm for slow ionic crosslinking. After standing for 24 hours, a homogeneous sodium alginate hydrogel with excellent mechanical strength was obtained. The obtained hydrogel was placed on a clean and flat glass plate and dried in a blast drying oven at 30°C for 24 hours to obtain a dense sodium alginate film.
[0051] Step five, 5.40 g of FeCl3·6H2O was dissolved in 200 ml of a mixed solution of deionized water and ethanol with a volume ratio of 10:3, and the sodium alginate film was immersed in the prepared 0.1 mol / L FeCl3·6H2O solution for ionic crosslinking for 24 hours. Then the polymer film after sufficient crosslinking was washed with deionized water, and after natural drying, a uniform and flat iron alginate film was obtained.
[0052] Step six, the (orange red) iron alginate film obtained in step five was sandwiched between two flat quartz glasses to form a sandwich structure, and was transferred to a tube furnace for calcination at 800°C under Ar atmosphere for 0.5 h, with an Ar gas flow rate of 0.7 L / min and a heating rate of 5°C / min. The carbonized iron / carbon composite material obtained after carbonization.
[0053] Step seven, the carbonization product obtained in step six was immersed in 300 mL of 2 mol / L hydrochloric acid solution and subjected to sufficient acid washing at 100°C for 25 h to remove carbonized iron.
[0054] Step eight, washing with deionized water until pH = 7, transfer to 110℃ vacuum drying oven for drying 24h to obtain sodium alginate derived carbon nanospheres self-assembled film electrode.
[0055] Figure 1 Optical photograph of the homogeneous sodium alginate hydrogel obtained in step four of the present example.
[0056] Figure 2 Scanning electron microscope image of the carbon nanospheres self-assembled film electrode obtained in the present example; as can be seen from the figure, the thickness of the film electrode is about 21μm, which is self-assembled by carbon nanospheres with a diameter of 50-100nm, and such self-assembled configuration spontaneously forms a three-dimensional continuous electron / ion transmission network.
[0057] Figure 3 X-ray diffraction pattern of the carbon nanospheres self-assembled film electrode obtained in the present example; as can be seen from the figure, the (002) peak contains a broad peak at ~22° and a shoulder peak at ~26°, and such asymmetric peak shape indicates the transformation of the existing form of carbon from amorphous to graphite.
[0058] Figure 4 N2adsorption / desorption isotherm and pore size distribution of the carbon nanospheres self-assembled film electrode obtained in the present example; as can be seen from the figure, the BET specific surface area of the carbon film is 229m 2 g -1 , the total pore volume is 0.302cm 3 g -1 , and the pore size is widely distributed in the mesoporous range of 4-50nm.
[0059] Figure 5 Rate performance of the carbon nanospheres self-assembled film electrode obtained in the present example as a sodium ion negative electrode material; as can be seen from the figure, the density of the film electrode is 1.18g cm -3 , the average volumetric capacity of the film electrode is 214.2mA h cm -1 at a small current density of 0.05A g -3 , the specific capacity attenuates slowly with the increase of current density, and even at an ultrahigh current density of 50Ag -1 , the film electrode can still retain a high volumetric capacity of 107mA h cm -3 .
[0060] Figure 6 Sodium ion diffusion coefficient of the carbon nanospheres self-assembled film electrode obtained in the present example; as can be seen from the figure, the sodium ion diffusion coefficient thereof is 2.53*10 -9 ~1.12*10 -8 cm 2 s -1 .
[0061] Electrochemical test conditions are as follows: the thin film electrode obtained in the present example is used as the working electrode, a metal sodium sheet is used as the reference electrode and the counter electrode, 1 M NaPF6 (the solvent is diethylene glycol dimethyl ether, DEGDME) is used as the electrolyte, and Whatman GF / D glass fiber is used as the separator to assemble a 2032 type button cell. Galvanostatic charge-discharge tests (GCD) at different current densities are carried out at room temperature to obtain the rate performance of the electrode. The sodium ion diffusion coefficient is measured using the galvanostatic intermittent titration technique (GITT). Specifically, before testing, the sodium ion half-cell is cycled for three cycles at a current density of 0.05 A g -1 + / Na.
[0062] Example 2
[0063] Step one: 1.0 g of sodium alginate is dissolved in 50 ml of deionized water, and after being stirred for 48 h, a 2 wt.% sodium alginate solution is obtained.
[0064] Step two: 0.15 g of calcium carbonate and 0.20 g of gluconolactone are weighed into 25 ml of deionized water, respectively, and ultrasonic stirring is performed to form a 0.6 wt.% CaCO3 suspension and a 0.8 wt.% gluconolactone solution.
[0065] Step three: the solution prepared in step two is added to the solution prepared in step one, and after being uniformly stirred by magnetic stirring, ultrasonic treatment is performed for 20 s to remove air bubbles.
[0066] Step four: immediately transfer to a culture dish with a height of 3 mm for slow ionic crosslinking. After standing for 24 hours, a homogeneous sodium alginate hydrogel with excellent mechanical strength is obtained. The obtained hydrogel is placed on a clean and flat glass plate and dried in a blast drying oven at 30°C for 24 hours to obtain a dense sodium alginate film.
[0067] Step five: 5.40 g of FeCl3·6H2O is dissolved in 200 ml of a mixed solution of deionized water and ethanol with a volume ratio of 10:3, and the film is immersed in the prepared 0.1 mol / L FeCl3·6H2O solution for ionic crosslinking for 24 hours. Then the polymer film after sufficient crosslinking is washed with deionized water, and after natural drying, a uniform and flat iron alginate film is obtained.
[0068] Step six, sandwich the orange iron alginate film obtained in step five between two flat quartz glass, transfer to the tube furnace, calcine at 700℃ for 0.5h under Ar atmosphere, the flow rate of Ar atmosphere is 0.8L / min, the heating rate is 4℃ / min, and the obtained carbonized iron / carbon composite material after carbonization.
[0069] Step seven, immerse the carbonized product obtained in step six in 300ml of 2mol / L hydrochloric acid solution, and perform sufficient acid washing at 100℃ for 30h to remove carbonized iron.
[0070] Step eight, wash with deionized water until pH=7, and transfer to a vacuum drying oven at 110℃ for sufficient drying for 24h to obtain a sodium alginate derived carbon nanosphere self-assembled film electrode.
[0071] Example 3
[0072] Step one, dissolve 1.0g of sodium alginate in 50ml of deionized water, and after sufficient stirring for 48h, obtain a 2wt.% sodium alginate solution.
[0073] Step two, respectively weigh 0.15g of calcium carbonate and 0.20g of gluconolactone into 25ml of deionized water, ultrasonic and stir to form a 0.6wt.% CaCO3 suspension and a 0.8wt.% gluconolactone solution.
[0074] Step three, add the solution prepared in step two to the solution prepared in step one, and after uniform magnetic stirring, remove the bubbles by ultrasonic treatment for 20s.
[0075] Step four, immediately transfer to a culture dish with a height of 3mm for slow ionic crosslinking. After standing for 24h, a homogeneous sodium alginate hydrogel with excellent mechanical strength is obtained. Place the obtained hydrogel on a clean flat glass plate, and dry in a 30℃ air drying oven for 24h to obtain a dense sodium alginate film.
[0076] Step five, weigh 5.40g of FeCl3·6H2O, dissolve in 200ml of a mixed solution of deionized water and ethanol with a volume ratio of 10:3, immerse the film in the prepared 0.1mol / L FeCl3·6H2O solution, and ionic crosslink for 24h. Then wash the polymer film after sufficient crosslinking with deionized water, and naturally dry to obtain a uniform and flat iron alginate film.
[0077] Step 6: The (orange-red) iron alginate film obtained in Step 5 is sandwiched between two flat quartz glasses to form a sandwich structure. It is then transferred to a tube furnace and calcined at 850°C for 1 hour under an Ar atmosphere with a flow rate of 0.6 L / min and a heating rate of 6°C / min. The resulting iron carbide / carbon composite material is obtained after carbonization.
[0078] Step 7: Immerse the carbonized product obtained in Step 6 in 300 mL of 2 mol / L hydrochloric acid solution and perform thorough acid washing at 100°C for 20 h to remove iron carbide.
[0079] Step 8: Wash with deionized water until pH=7, then transfer to a vacuum drying oven at 110℃ and dry thoroughly for 24 hours to obtain the sodium alginate-derived carbon nanosphere self-assembled thin film electrode.
[0080] Figure 7 The graph shows the rate performance of the carbon nanosphere self-assembled thin film electrodes obtained in Examples 2 and 3 as sodium ion anode materials; as can be seen from the graph, the densities of the thin film electrodes obtained in Examples 2 and 3 are 1.15 g / cm³, respectively. -3 1.20g cm -3 Under the same test conditions as in Example 1, the thin-film electrode was tested at 0.05 A g. -1 The average volumetric specific capacity at the current density was 194.5 and 189.1 mA h cm⁻¹, respectively. -3 Furthermore, as the current density increases, the specific capacity decays more slowly, exhibiting excellent volumetric specific capacity and rate performance.
[0081] Comparative Example 1
[0082] The preparation method of this comparative example is basically the same as that of Example 1, except that the calcium source is replaced by an aqueous solution of CaCl2 instead of a suspension of sparingly soluble calcium salts such as CaCO3.
[0083] Specifically, in step two, weigh 0.15g of calcium chloride and add it to 25ml of deionized water, then sonicate and stir to form a 0.6wt.% CaCl2 solution. In step three, transfer the sodium alginate solution obtained in step one to a 3mm high petri dish and add the CaCl2 aqueous solution prepared in step two; or directly pour the sodium alginate solution obtained in step one into the CaCl2 aqueous solution. In step four, let it stand for 12 hours to allow the sodium alginate to react with the CaCl2. 2+ Fully cross-linked.
[0084] The hydrogel obtained in this comparative example has a heterogeneous structure. (See attached...) Figure 8 As shown, where Figure 8 a is an optical photograph of the hydrogel obtained by adding CaCl2 solution to sodium alginate solution. Figure 8b is an optical photograph of the hydrogel obtained by adding the sodium alginate solution into the CaCl2solution. Due to the rapid cross-linking of sodium alginate and Ca2+in the aqueous solution, the obtained hydrogel all forms a heterogeneous structure with a calcium alginate surface layer wrapping the sodium alginate solution, which cannot be used for the preparation of dense sodium alginate films subsequently. 2+
[0085] Comparative Example 2
[0086] The preparation method of the present comparative example is basically the same as that of Example 1, except that the homogeneous hydrogel obtained in Step Four is directly immersed in the prepared FeCl3·6H2O solution for ion cross-linking, and then the water is removed by freeze-drying. 3+
[0087] Specifically, Step Four, immediately transfer to a culture dish with a height of 3 mm for slow ion cross-linking. After standing for 24 hours, a homogeneous sodium alginate hydrogel with excellent mechanical strength is obtained. Step Five, weigh 5.40 g of FeCl3·6H2O and dissolve it in 200 ml of a mixed solution of deionized water and ethanol with a volume ratio of 10:3, and directly immerse the homogeneous hydrogel obtained in Step Four in the prepared 0.1 mol / L FeCl3·6H2O solution for ion cross-linking for 24 hours. After washing with deionized water, freeze-drying is carried out at -60°C and a pressure of 1 Pa for 24 h.
[0088] The hydrogel obtained in the present comparative example is a brittle and loose porous iron alginate aerogel, as shown in Figure 9 . The product obtained after carbonization and acid washing is a porous carbon powder, as shown in Figure 10 .
[0089] Mix the porous carbon powder sample (80 mg) obtained in the present comparative example with commercial conductive carbon black and binder (polyvinylidene fluoride dissolved in N-methyl pyrrolidone, 0.025 g ml -1 ) at a mass ratio of 8:1:1, and after sufficient stirring, form a slurry, which is coated on a copper foil, vacuum dried at 110°C for 12 h, and then cut into pieces with a diameter of 12 mm using a slicing machine to obtain a porous carbon powder-based electrode sheet. According to the electrode loading and thickness, the electrode density is calculated to be 0.51 g cm -3 , which is much smaller than the density of the thin film electrode obtained in the example (1.15-1.20 g cm -3 ).
[0090] Figure 11 Figure is the rate performance graph of the porous carbon powder-based electrode obtained in the present comparative example as a sodium ion negative electrode material. As can be seen from the figure, under the same test conditions as in Example 1, the obtained porous carbon powder-based electrode has a specific capacity of 0.05 and 5 Ag -1 The average volumetric capacity at a current density of 100 mA g -3 is only 87.7 and 55.4 mA h cm
[0091] Figure 12 The sodium ion diffusion coefficient of the porous carbon powder-based electrode obtained in the present comparative example is 9.85*10 -10 ~ 5.38*10 -9 cm 2 s -1 .
[0092] The above describes specific embodiments of the present application. It should be understood that the present application is not limited to the specific embodiments described above, and various modifications or changes can be made by those skilled in the art within the scope of the claims, which does not affect the essential content of the present application.
Claims
1. A method for preparing a high magnification carbon nanosphere self-assembled thin film electrode, characterized in that, The method comprises the following steps: Step one: adding the insoluble calcium salt into the sodium alginate solution, and then adding the aqueous solution of gluconolactone to obtain the sodium alginate hydrogel; Step two: evaporative-induced drying the sodium alginate hydrogel to obtain the sodium alginate film; Step three: Soak the sodium alginate film in a solution of Fe 3+ to cross-link and form an iron alginate film. Step four: calcining and carbonizing the iron alginate film, and then etching by acid washing to obtain the carbon nanospheres self-assembled film electrode.
2. The production method according to claim 1, characterized by, In step one, the insoluble calcium salt includes any one of the nano-CaCO3 suspension and the nano-CaSO4 suspension.
3. The preparation method according to claim 1, characterized in that, In step one, the mass ratio of the insoluble calcium salt, the gluconolactone and the sodium alginate is 5-7:7-9:
40.
4. The method of claim 1, wherein, In step two, the temperature of the evaporative-induced drying is 20-40℃, and the time is 20-30h.
5. The preparation method according to claim 1, characterized in that, In step three, the Fe 3+ The solution contains one of Fe(NO3)3, FeCl3, Fe2(SO4)3; the Fe 3+ The concentration of the solution is 0.08-0.15 mol / L.
6. The method of claim 1, wherein, In step three, the crosslinking time is 20-30h.
7. The preparation method according to claim 1, characterized in that, In step four, the calcining and carbonizing is performed at a temperature increasing rate of 4-6℃ / min to 750-850℃, and the temperature is kept for 0.5-1h.
8. The method of claim 1, wherein, In step four, the acid used for the etching by acid washing includes 1.8-2mol / L hydrochloric acid, the temperature of the etching by acid washing is 90-110℃, and the time is 20-30h.
9. The method of claim 1, wherein, In step four, after the etching by acid washing, the carbon nanospheres self-assembled film electrode is obtained by cleaning and vacuum drying, and the temperature of the vacuum drying is 100-110℃, and the time is 20-30h.
10. The high-rate carbon nanospheres self-assembled film electrode prepared by the method of any one of claims 1-9.
